PENGARUH PENGUNAAN BUKU AJAR DENGAN PENDEKATAN KONSTRUKTIVISTIK DAN MULTI REPRESENTASI PADA MATERI IKATAN KIMIA - Yuniarti, Yuniarti; Enawaty, Eny; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine how much influence the learning of using textbooks with constructivist and multirepresentative approaches to student learning Â outcomes in the material of ionic bonds and covalent bonds. The population of this study was all students of academic class. The sampling technique used is saturated sampling. Data collection techniques used are measurement techniques and direct communication techniques. The assessment instrument used was the learning achievement test. The sample used in this study was class XA as a control class and class XB as an experimental class. The design used in this study is the control group pretest-posttest design. Assumed the data come from the same variance. Based on the t-independent test, a sig value of 0,000 (<0.05) was obtained, meaning that there were differences in learning outcomes between the control class and the experimental class. Differences in learning outcomes between control class students and experimental class students who are given learning by using textbooks with constructivist and multirepresentative approaches. The effect of learning using books with a constructivist and multi-representation approach. gives an effect of 76% on learning outcomes in the material of ionic bonds and covalent bonds of class X students of SMA 2 AMBAWANG.Keywords: Constructivist and Multi-Representation Textbook MediaÂ